Utility of Magnetic Resonance Imaging for Localizing Prostate Cancer Near the Urethra in Men Who Are Candidates for Focal Gland Ablation. Issue 5 (8th May 2023) - Patel, Neal; Hughes, Alexa; Zhang, JJ H.; Brisbane, Wayne; Rastegarpour, Ali; Afsahir, Sohrab; Kwan, Lorna; Nguyen, Anissa V.; Sisk, Anthony; Raman, Steve; Reiter, Robert
Abstract : Purpose: Given that treatment near the urethra is often limited to reduce side effects, in this study we aim to determine whether prostate MRI can accurately identify the distance of prostate cancer to the urethra in a cohort of men who were potential candidates for focal gland ablation. Materials and Methods: A single-institution analysis was performed of men who underwent MRI, targeted biopsy, and radical prostatectomy from July 2012 to April 2021. Men who were candidates for focal gland ablation were identified. The ability of MRI to identify prostate cancer within 5 mm of the prostatic urethra as confirmed on whole-mount pathology was assessed. Multivariate regression was utilized to determine characteristics associated with prostate cancer within 5 mm of the urethra on whole-mount pathology. Results: In 48 out of 67 men (72%), the tumor was within 5 mm of the urethra on whole-mount pathology. MRI was concordant with whole-mount pathology in 49 out of 67 men (73%). The sensitivity of MRI for identifying cancer within 5 mm of the urethra was 77% (65%-89%) and the specificity was 63% (42%-89%). The positive predictive value was 84% (range 73%-95%) and negative predictive value was 52% (32%-73%). In adjusted analysis, PSA density and Prostate Imaging-Reporting and Data System were not significantly associated with having prostate cancer within close proximity of the urethra. Conclusions: A significant number of men who are potential candidates for focal gland ablation have cancer within close proximity to the urethra that could serve as a significant source of in-field recurrence. The sensitivity of MRI for identifying these lesions is 77% and can be used to further improve patient selection for focal gland ablation.